Investigation of the fluctuation of the static axial rigidity for double-nut preloaded ball screws - Kai Wang; Chang-guang Zhou; Yi Ou (Advances in Mechanical Engineering, 2019)
This article aims to investigate the fluctuation of the static rigidity for preloaded ball screws. Based on the correlation between preload and friction torque, a new model to calculate the contact rigidity by friction torque is proposed. Meanwhile, a novel test bench is constructed to measure the static stiffness at different positions. The experimental results agree well with the theoretical values, which proves the validity of the model. Furthermore, it is found that the screw shaft rigidity has the greatest influence on the system stiffness fluctuation, compared to the bearing rigidity, and the torsional rigidity. For the feed system, increasing the bearing rigidity, which is the lowest stiffness of the whole system, is an effective method to increase the system stiffness. The study provides an accurate method to obtain the stiffness fluctuation in the effective travel of ball screws, which is significant for improving the positioning accuracy of ball screws and computer numerical control machine tools.